PERAN STRATEGIS MEDIA SOSIAL DALAM POLITIK: TINJAUAN BUKU SOCIAL MEDIA IN POLITICS - Hafsah Juni Batubara (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2024)
The modern world, especially through social media, has changed tremendouslydue to advances in information technology. By analyzing severalcase studies, this article discusses the role of social media in politics. These studies illustrate the political power thatthese platforms can harness. The study explores how political actorsuse social media such as Facebook, Twitter, and Instagramto mobilize supporters, influence public opinion, andset political agendas. The case studies include politicalcampaigns, social movements, and protests led by social media. The focusof the study is on how it impacts election outcomes, how it influences government policies, andhow social polarization and the spread of misinformation emerge.The study shows that social media not only functions as acommunication tool but also as a political force that caninfluence democracy in good or bad ways. Itprovides an understanding of how social media caninfluence politics today and the moral challenges that stakeholders must face.